Anemia in patients admitted to a hospital in Teixeira Soares-PR - Modrow, Juliana Cristina; Luz, Natany Aparecida; Martins, Vânia Regina (Seven Editora, 2023)
Anemia is characterized by low hemoglobin concentration in the blood and it is estimated that more than two billion people in the world are anemic. The blood count is the test that contains the result of the measurement of hemoglobin in the blood, and to be indicative of anemia, in females hemoglobin must be below 12g/dL and in males below 13g/dL. The objective of this research was to determine the frequency of anemia in hospitalized patients, as well as the treatment prescribed for anemia at the Hospital de Teixeira Soares-PR, from April 2020 to January 2021. The sample consisted of data from medical records and results blood counts of all patients hospitalized during the period and selected patients with anemia. Morphological classification of anemia, classification of diagnosis prescribed by the hospital and treatment performed were performed. As a result, it was found that the prevalence of anemia was 21.33% among hospitalized patients, and 42.19% were anemia due to chronic disease. Most (68.75%) had normocytosis and normochromia. The contributions of this study were to highlight the high prevalence of anemia in hospitalized patients; that the most frequent anemia was anemia of chronic disease and show the need for greater care on the part of health professionals in the interpretation of these anemic cases. DOI:https://doi.org/10.56238/alookdevelopv1-076